Find the Function !

Algebra Level 5

f ( n ) = cot 2 π n + cot 2 2 π n + cot 2 3 π n + + cot 2 ( n 1 ) π n f(n) =\cot^2 \frac \pi n + \cot^2\frac {2\pi}n + \cot^2 \frac {3\pi}n + \cdots + \cot^2 \frac {(n-1)\pi}n

Let f ( n ) f(n) be defined as above for n > 1 N n > 1 \in \mathbb N . Find f ( 50 ) f(50) .


The answer is 784.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Manan Agrawal
May 18, 2018

Let

x = i . c o t k π n x=-i.cot\frac { k\pi }{ n }

x + 1 x 1 = e i 2 π n \large\large\large\large\therefore \quad \frac { x+1 }{ x-1 } ={ e }^{ i\frac { 2\pi }{ n } }

( x + 1 x 1 ) n = 1 \large\Rightarrow \quad { \left( \frac { x+1 }{ x-1 } \right) }^{ n }=1

( x + 1 ) n ( x 1 ) n = 0 \therefore \quad { (x+1) }^{ n }-{ (x-1) }^{ n }=0

C 1 x n 1 + C 3 x n 3 + . . . . + C n x 0 = 0 \therefore \quad { C }_{ 1 }{ x }^{ n-1 }+{ C }_{ 3 }{ x }^{ n-3 }+....+{ C }_{ n }{ x }^{ 0 }=0

Note that root of this equation is i . c o t ( k π n ) -i.cot\left( \frac { k\pi }{ n } \right)

k = 1 n 1 ( i . c o t k π n ) 2 = ( k = 1 n 1 ( i . c o t k π n ) 2 ) 2 1 p q ( n 1 ) ( ( i . c o t p π n ) . ( i . c o t q π n ) ) \therefore \quad \displaystyle \sum _{ k=1 }^{ n-1 }{ { \left( i.cot\frac { k\pi }{ n } \right) }^{ 2 } } =(\sum _{ k=1 }^{ n-1 }{ { \left( -i.cot\frac { k\pi }{ n } \right) }^{ 2 } } )-2\sum _{ 1\le p \le }{ \sum _{ q\le (n-1) }{ \left( \left( i.cot\frac { p\pi }{ n } \right) .\left( i.cot\frac { q\pi }{ n } \right) \right) } }

= 0 2. C 3 C 1 \large\qquad \qquad \qquad \qquad \qquad =\quad 0-\frac { 2.{ C }_{ 3 } }{ { C }_{ 1 } }

f ( n ) = ( n 1 ) ( n 2 ) 3 \large\large\therefore \quad \boxed { f\left( n \right) =\frac { (n-1)(n-2) }{ 3 } }

Mark Hennings
May 17, 2018

In this problem I showed that g ( n ) = m = 1 n 1 cot 2 m π 2 n = 1 3 ( n 1 ) ( 2 n 1 ) g(n) \; = \; \sum_{m=1}^{n-1} \cot^2 \tfrac{m\pi}{2n} \; = \; \tfrac13(n-1)(2n-1) By symmetry it is clear that f ( 2 n ) = 2 g ( n ) f(2n) \; = \; 2g(n) and hence f ( 50 ) = 2 3 × 24 × 49 = 784 f(50) \; = \; \tfrac23 \times 24 \times 49 = \boxed{784}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...